Efektivitas Program Bantuan Langsung Tunai Pada Era Pandemi Covid-19 Di Desa Haloban Kecamatan Pulau Banyak Barat - Alvi Rizaldi (Universitas Muhammadiyah Sumatera Utara, 2022)
The majority of the people here make a living as fishermen. Due to Covid-19, access to goods and services is also limited and has an impact on the community's economy, and not a few people have been laid off from their workplaces in the city, and are forced to return to their villages. BLT-Dana Desa is one of the programs issued by the Indonesian government to overcome the impact of economic factors affected by the Covid-19 pandemic in the form of financial assistance provided to poor families, sourced from the Village Fund revenue budget. The social service program planning process is carried out through discussion and general deliberation by village officials. The process of organizing the social service program has been given the person in charge of the BLT-DD distribution activities, the distribution of BLT-DD is carried out once a month with a direct distribution process given by the village government to KPM BLT-DD, Monev which is carried out after the implementation of the BLT-DD Distribution Program DD is evaluated by the village head and his apparatus. The BLT-DD program was deliberately issued by the government to overcome the decline in public finances due to the Covid-19 outbreak. Measures of program effectiveness, namely; understanding of the program, right on target, on time, the achievement of goals and real changes can be concluded that it has not been running effectively